Crisis communication and ethics: The role of public relations - JIN, Yan (Institutional Knowledge at Singapore Management University, 2018)
Purpose: The purpose of this paper is to explore the veracity of the contingency model of ethical crisis communication by examining the factors of influence in a time of crisis including what constitutes ethics in a time of crisis; the role of public relations (PR) practitioners as the “moral conscience” of an organization and perceptions of the PR’ role within top management. Design/methodology/approach: In-depth interviews were conducted among ten senior PR managers with crisis communication experience in North America. Findings: This research identifies and investigates six ethical variables – the nature of the crisis, the role of top management, the activism of stakeholders, government regulation/intervention, the diversity of cultures and the exposure to external business environments – and their potential influences on an organization’s communication practices. Research limitations/implications: The qualitative approach does not produce generalizable results. In addition, the authors could have interviewed more people, although the authors have reached information saturation in analyzing the interview data based on the ten interviews conducted. Practical implications: Insights from this exploratory study contribute to answering the “how” questions with empirical data that enhance the clarity on the roadmap of ethical factors in crisis communication practice. Originality/value: Unlike other conceptual work that explores moral philosophies in ethics, this study aims to offer a practical approach – rather than a philosophical argument and persuasion – that is rooted in the practitioner’s world.